Effectivity of Biomarker-Guided Multidisciplinary Approach to Cardio Renal Syndrome - Aftab Rabbani, Abdul Basit Niazi, Mohammad Atiq Ur Rehman, Syed Raza Abbas, Anam, Ejaz Ahmad, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim of Study: To evaluate clinical features, early biomarkers, pathophysiological mechanisms, and treatment outcomes of cardiorenal syndrome (CRS) in hospitalized patients. Study Duration: January 2022 to March 2023. Study Place: Niazi Medical & Dental College, Sargodha & Sharif Medical Hospital, Lahore, Pakistan. Study Type: Prospective study. Methodology: 150 patients with CRS (types 1–5) were enrolled. Serum biomarkers (NT-proBNP, NGAL, Cystatin C, Troponin-I), renal/cardiac function tests, and echocardiography were analyzed. Treatment response to diuretics, ACE inhibitors, and renal replacement therapy (RRT) was assessed. Results: NT-proBNPand NGAL were elevated in 92% and 88% of CRS cases, respectively. 34% progressed to acute kidney injury (AKI); 22% required RRT. Mortality was 18%, highest in CRS type 3 (Table 4). Discussion: Early biomarker elevation (NGAL, Cystatin C) preceded creatinine rise by 24–48 hours. Hemodynamic instability and neurohormonal activation were key pathophysiological drivers. Tailored diuretic and RRT protocols improved outcomes. Conclusion: NGAL and NT-proBNP enable early CRS diagnosis. Multidisciplinary management reduces mortality. Keywords: Cardiorenal syndrome, NGAL, NT-proBNP, acute kidney injury, heart failure, biomarker.